ANFIS and statistical based approach to prediction the peak pressure load of concrete pipes including glass fiber - Emiroğlu, Mehmet; Beycioğlu, Ahmet; Yıldız, Servet (My University, 2012)
In this paper, Adaptive Neural Fuzzy Inference System (ANFIS) and Multiple Linear Regression (MLR) models are discussed to determine peak pressure load measurements of the 0, 0.2, 0.4 and 0.6% glass fibers (by weight) reinforced concrete pipes having 200, 300, 400, 500 and 600 mm diameters. For comparing the ANFIS, MLR and experimental results, determination coefficient (R2), root mean square error (RMSE) and standard error of estimates (SEE) statistics were used as evaluation criteria. It is concluded that ANFIS and MLR are practical methods for predicting the peak pressure load (PPL) values of the concrete pipes containing glass fibers and PPL values can be predicted using ANFIS and MLR without attempting any experiments in a quite short period of time with tiny error rates. Furthermore ANFIS model has the predicting potential better than MLR.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Concrete pipe; Peak pressure load; Glass fiber; Multiple Linear Regression; ANFIS